Haplotype variation of estrogen receptor-? (ER-?) gene exon 4 in Turkish sheep breeds - Ozmen, O.; Seker, I.; Kul, B. Cinar; Ertugrul, O. (Pleiades Publishing Inc, 2012)
Estrogen receptor a (ER alpha) gene has previously been found related with sexual development and reproduction. In this study, on the basis of the sequences of human, cattle and caprine estrogen receptor alpha (ER alpha) genes, available in the GenBank database, sets of PCR primers were designed and used to amplify the ovine ER alpha gene exon 4 region. We identified six single nucleotide polymorphisms (SNP) in the ER alpha exon 4. Some variations determined for exon 4 g.43A > G, p.T43A; g.49C > T, p.L49F; g.178A > T, p.T178S led to changes in the amino acids, but no amino acid changes were determined in g.18G > C, g.27C > T, g.96G > A. These fragments were deposited in the GenBank database under accession numbers: JF262030-JF262035. It was noted in particular that White Karaman and Awassi breeds were similar to each other, whereas the Chios breed had a different variation.
Keywords: Litter Size; Statistical Tests; Beta; Polymorphism; Association; Neutrality; Pigs; Esr1